Equatorial Pacific productivity changes near the Eocene‐Oligocene boundary. (3rd September 2014) - Moore, T. C.; Wade, Bridget S.; Westerhold, Thomas; Erhardt, Andrea M.; Coxall, Helen K.; Baldauf, Jack; Wagner, Meghan
Abstract There is general agreement that productivity in high latitudes increased in the late Eocene and remained high in the early Oligocene. Evidence for both increased and decreased productivity across the Eocene‐Oligocene transition (EOT) in the tropics has been presented, usually based on only one paleoproductivity proxy and often in sites with incomplete recovery of the EOT itself. A complete record of the Eocene‐Oligocene transition was obtained at three drill sites in the eastern equatorial Pacific Ocean (ODP Site 1218 and IODP Sites U1333 and U1334). Four paleoproductivity proxies that have been examined at these sites, together with carbon and oxygen isotope measurements on early Oligocene planktonic foraminifera, give evidence of ecologic and oceanographic change across this climatically important boundary. Export productivity dropped sharply in the basal Oligocene ( 33.7 Ma) and only recovered several hundred thousand years later; however, overall paleoproductivity in the early Oligocene never reached the average levels found in the late Eocene and in more modern times. Changes in the isotopic gradients between deep‐ and shallow‐living planktonic foraminifera suggest a gradual shoaling of the thermocline through the early Oligocene that, on average, affected accumulation rates of barite, benthic foraminifera, and opal, as well as diatom abundance near 33.5 Ma. An interval with abundant large diatoms beginning at 33.3 Ma suggests an intermediate thermocline depth, which was followed by further shoaling, a dominance of smaller diatoms, and an increase in average primary productivity as estimated from accumulation rates of benthic foraminifera.